Social Media Adoption and Business Performance: Evidence from Employees of Tranos Contracting Limited, Nigeria - Oladapo, Fasanmi Olumuyiwa; Alawode, Olufemi Peter; Moses, Sodeinde Gbemi; Oladipo, Temidayo David; Ronke, Adeyefa Christianah (Universitas Medan Area, 2025)
In the digital age, social media provides a new avenue for corporate communication, employee engagement, marketing, and brand management. The exponential growth of Facebook, LinkedIn, Instagram, and Twitter has laid the new paradigm for businesses to interact with stakeholders and manage organizational performance. This study focuses on how the use of social media affects organizational performance, specifically through the study of Tranos Contracting Limited, Lagos. With the rise of such digital communication, it is imperative that any platform like Twitter and Instagram be used for visibility, engagement, and performance enhancement. The study was descriptive survey and involved 144 employees of the organization. Data were collected through a structured questionnaire and analysed using multiple regression techniques. The findings reveal that both Twitter and Instagram usage influence organizational performance; however, Instagram does so more significantly due to its visual and promotional nature. Twitter contributes positively as well, especially with its instant updates and professional engagements. The study concludes that the strategic use of social media helps immensely in aiding internal communication, stakeholder engagement, and brand perception. It recommends that organizations integrate social media strategies, allocate resources for content development, and train their staff in the effective use of these platforms.